17. IMPLEMENTASI REGIONAL COOPERATION AGREEMENT ON COMBATING PIRACY AND ARMED ROBBERY AGAINST SHIP IN ASIA (RECAAP) DALAM MENANGANI KASUS PEROMPAKAN DI LAUT TIONGKOK SELATAN PERIODE 2009-2014 - Ezza Navsar Fisabilli; Tri Cahyo Utomo; Shary Charlotte P (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2016)
Maritime piracy and armed robbery against ship remains important issue due to its nature as athreat to international security, inflicting impacts beyond national borders. Pirate attacks inSouth China Sea is not only disrupting regional security, but also alarms claimant statesaround the sea border. ReCAAP is an agreement signed by 14 countries on 11 November2004. To this date, 20 countries had joined ReCAAP to combat piracy and armed robbery inAsia. The main objective of this research is to analyse piracy and armed robbery against shipactivities in South China Sea in 2009-2014 and also ReCAAP implementation in combatingSouth China Sea piracy and armed robbery against ship in 2009-2014. This explanativeresearch attempts to explain piracy and armed robbery against ship activities and also to giveexamples of ReCAAP implementation in South China Sea. By using neoliberalism paradigm,this research finds that this cooperation which is based on absolute gains and common interestwas implemented through three pillars, that is Information Sharing Center (ISC), CapacityBuilding, and Cooperative Arrangements. Focal Point is the main mechanism in thiscooperation.